A Retrospective Study on Drug Induced Complications Among Different Age Groups - Sai, P. Shoba; Kiranya, Ch.; Savitha, K.; Manasa, A.; Ali Sameera, Amatul; Lateef Amrohi, Nazia (Journal of Neonatal Surgery, 2025)
Aim And Objective: This study is aimed to perform a retrospective study on drug induced complications among different age groups. Methodology: This retrospective study was conducted at Aware Global Hospital in Hyderabad aimed to investigate the prevalence of drug induced complications among them. Over a 6 months period, data was collected from 85 patient cases from general medicine department. Results: The research findings reveal a higher drug induced complications incidence in males (54%) than females (46%), predominantly drug induced hypoglycemia (27.05%). According to WHO classification of age groups elderly age group (60-74 years) accounted for maximum DID’s (45.58%). Hypoglycemia (27.05%), hypersensitivity (11.80%), hyponatremia (8.23%), hyperglycemia (8.23%), hepatopathy (7.05%), cough (5%), gastritis (3.52%), AKI (2.4%), parkinsonism (2.4%), pedal edema (2.4%), oral bleed (2.4%) was some of the drug induced complications involved. The 61-70 age group faces a higher risk (31%), often linked to comorbidities. Conclusion: The study concluded that a total of 85 patients with drug induced complications has been found a peak in the age group 61-70, with a higher incidence in males compared to females. Usage of anti-diabetic agents, anti-hypertensives, antibiotics, corticosteroids, NSAID’s, anti-tubercular agents, anti-coagulants, anti-platelets, anti-psychotics were usually involved in causing complications.